The Effects of Seeding Time on the Seed Yield of Annual Ryegrass. (1st May 2013) - Coulman, Bruce; Loeppky, Heather; Entz, Martin
Abstract : Annual ryegrass ( Lolium multiflorum Lam.) is an annual grass that has shown promise as a fall grazing crop in the northern Great Plains of western Canada. Seed crops of this species are also grown in the region. Late fall (dormant) seedings of annual grain crops have often been found to produce higher seed yields than spring seedings. This study compared the stand establishment and seed yields of late fall and spring seedings of annual ryegrass cultivar Barspectra at three locations in western Canada; Melfort, SK; Outlook, SK; and Carman, MB. Stand establishment was assessed by measuring tiller density in the month of June and these densities were always greater for spring than late fall seedings. For 4 of the 7 site‐years in the study, fall seedings produced higher seed yields than spring seedings; for 1 site‐year, spring seedings produced higher seed yields than fall seedings; and for 2 site‐years, there were no differences between the two seeding times. Thus, lower spring tiller densities for fall seedings did not result in lower seed yields. It was concluded that the late fall seeding time was a viable alternative to a spring seeding for producers of annual ryegrass seed in western Canada. Future research should investigate earlier fall seeding dates.